Analisis Kerusakan Dini Transformator Distribusi Ulp Padangan Penyulang Watu Jago Menggunakan Metode Reliability, Availability, Maintainability (RAM) - Suprawikno, Suprawikno; Adiaksa, Irgianto Candra (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2024)
Electricity distribution transformers have an important role in converting high voltage into low voltage suitable for consumers. These transformers operate continuously for 24 hours in the distribution of electricity. Especially when distributing extra high voltage, supervision is required to maintain safety and performance. The Reliability, Availability, Maintainability (RAM) method is used to analyze the effectiveness and potential damage to the transformer. The analysis results show that in January, the Mean Time Between Failures (MTBF) was 372 hours with 2 failures, while in June only 1 failure. Mean Time To Repair (MTTR) in January 1.03 hours with 2 repairs, while in June only 1 repair with 0.8 hours. Failure Rate January 0.269%, June 0.139%. Transformer reliability over the last 6 months is 99.94% and will decrease. Availability in the last 6 months is 99.94%, but will decrease. Maintainability tends to be lower and will decrease further. The analysis recommends replacing the transformer in the next 1,77 years as the ease of repair is decreasing. Although generally used for 5-10 years, the level of ease of repair affects the effective use in electricity distribution.